The Purse Seine Fleet Compliance strategy to Fishing Regulations at Nizam Zachman Fishing Port, Jakarta: STRATEGI PENINGKATAN KEPATUHAN ARMADA PURSE SEINE TERHADAP REGULASI PENANGKAPAN IKAN DI PPS NIZAM ZACHMAN JAKARTA - Gugun Gunawan; Ari Purbayanto; Iin Solihin (Bogor Agricultural University, 2021)
Importer countries of Indonesian fishery products, such as European Union countries (EU) and the United States (USA), are very concerned about the treacebility of fishery products, which lead to some rejection of fishery products obtained from illegal, unreported and unregulated activities (IUU Fishing) in NZFPJ. Approximately 231 vessels, 121 of it are purseiners, conducted fishing operations outside permitted fishing areas and at least 42 vessels were moored outside their assigned fishing ports. Considering the number of violations, this study is aiming at formulating strategies to improve compliance level of fishing vessels. Data from the case study were analyzed using Strengths Opportunities Weaknesses Threats (SWOT) method and Quantitative Strategic Planning Management (QSPM). The results showed that strategies to improve the compliance of purseiners to fishing regulations in NZFPJ are by developing an integrated fishing vessel monitoring system with relevant agencies conducting law enforcement in the field of marine and fishery. In addition, reward and punishment scheme along with education for fishermen and businessmen are required to improve awareness. Lastly, there is need to provide facilities and training to support the monitoring activities. Keywords: IUU fishing, NZFPJ, inspection.